Dynamics associated with the phenomenon of matrifocality (single motherhood) in Zimbabwe: a literature review - Kang’ethe, S.M.; Mafa, Itai (Kamla-Raj Enterprises, 2020)
The geometric increase in the rate of matrifocality or single motherhood in Zimbabwe is a huge cause of worry that needs to be addressed for the country to strengthen its family structures. The phenomenon has been associated with feminization of poverty, feminization of HIV/AIDS, child poverty and general despondency of the citizens generally. The article has used a review of literature methodology. Findings indicate that cultural erosion, increased space for women freedom, harsh economic conditions, modernization, globalization, westernization and industrialization have been identified as factors influencing single motherhood in Zimbabwe. Subsequently, the following have been identified as a way forward: implementing the free basic education policy; emphasizing, advocating, rejuvenating, repositioning and reclaiming cultural values; regulating and censoring the content of the media; and the use of specialized social welfare to handle single mothers.